Odžakluk-Timars in Bosnia and Herzegovina (Prilozi za orijentalnu filologiju, 2017)
In this paper the author summarizes some of the assumptions from his earlier study "Development of the Timar System in Bosnia and Herzegovina" (timar- feudal estate).The author thinks that the timar system in Bosnia and Herzegovina had developped in the san1e way as in other Balkan countries. According to him the Ottomans had already had a developped timar system at the time of the conquest of Bosnia and Herzegovina. In these regions they consistently applied the miri-land principle and they accepted into their feudal system representatives of the old feudal class - especially lower aristocracy - no matter whether they were islamized or not, taking into account nothing but the mentioned principle. Thus the assertation that the old aristocracy of Bosnia and Herzegovina retained their estates and priviledges by converting into Islam is nothing but a historical mistake.The author then deals with the question of the origin and development of odžakluk-timars in Bosnia and Herzegovina. He emphasizes the importance of this institution for the development of Bosnia and Herzegovina under the Ottoman rule from 17ct tili 19ct, providing the proof for his assumption that this institution has caused the mistake mentioned above. In connecton with these two problems the author considers the question of čifluk in Bosnia and Herzegovina explaining his attitude.All these reflections are based on numerous historical sources. The same author is working on their analysis at the